Reduced Graphene Oxide-Wrapped FeS2 Composite as Anode for High-Performance Sodium-Ion Batteries - Wang, Qinghong; Guo, Can; Zhu, Yuxuan; He, Jiapeng; Wang, Hongqiang (Nano-Micro Letters, 2017)
Iron disulfide is considered to be a potential anode material for sodium-ion batteries due to its high theoretical capacity. However, its applications are seriously limited by the weak conductivity and large volume change, which results in low reversible capacity and poor cycling stability. Herein, reduced graphene oxide-wrapped FeS2 (FeS2/rGO) composite was fabricated to achieve excellent electrochemical performance via a facile two-step method. The introduction of rGO effectively improved the conductivity, BET surface area, and structural stability of the FeS2 active material, thus endowing it with high specific capacity, good rate capability, as well as excellent cycling stability. Electrochemical measurements show that the FeS2/rGO composite had a high initial discharge capacity of 1263.2 mAh g−1 at 100 mA g−1 and a high discharge capacity of 344 mAh g−1 at 10 A g−1, demonstrating superior rate performance. After 100 cycles at 100 mA g−1, the discharge capacity remained at 609.5 mAh g−1, indicating the excellent cycling stability of the FeS2/rGO electrode. Highlights: 1 Reduced graphene oxide-wrapped FeS2 (FeS2/rGO) composite was synthesized by a facile two-step method. 2 The integral reduced graphene oxide networks not only connect the FeS2 nanoparticles but also prevent them from aggregating. 3 As anodes for sodium-ion batteries, the FeS2/rGO composite delivers high specific capacity and good cycling stability.